Impaired retention is responsible for temporal order memory deficits in mild cognitive impairment - Gillis, M. Meredith (2013)
Temporal order memory, or remembering the order of events, is critical for everyday functioning and is difficult for patients with mild cognitive impairment (MCI). It is currently unclear whether these patients have difficulty acquiring and/or retaining such information and whether deficits in these patients are in excess of “normal” age-related declines. Therefore, the current study examined age and disease-related changes in temporal order memory as well as whether memory load played a role in such changes. Young controls (n=25), older controls (n=34), and MCI patients (n=32) completed an experimental task that required the reconstruction of sequences that were 3, 4, or 5-items in length both immediately after presentation (i.e., immediate recall) and again following a 10-minute delay (i.e., delayed recall). During the immediate recall phase, there was an effect of age largely due to reduced performance at the two longest span lengths. Older controls and MCI patients only differed during the 5 span (controls > MCI). During the delayed recall, however, there were significant effects of both age and MCI regardless of span length. In MCI patients, immediate recall was significantly correlated with measures of executive functioning while delayed recall performance was only related to other memory tests. These findings suggest that MCI patients experience initial temporal order memory deficits at the point when information begins to exceed working memory capacity and become dependent on medial temporal lobe functioning. Longer-term deficits are due to an inability to retain information, consistent with the characteristic medial temporal lobe dysfunction in MCI.